7‐keto‐DHEAmetabolism in humans. Pitfalls in interpreting the analytical results in the antidoping field. Issue 11 (13th December 2019) - Martinez‐Brito, Dayamin; de la Torre, Xavier; Colamonici, Cristiana; Curcio, Davide; Botrè, Francesco
Abstract: 7‐keto‐DHEA (3β‐hydroxy‐androst‐5‐ene‐7, 17‐dione) is included in section S1 of the World Antidoping Agency (WADA) List of Prohibited Substances. The detection of its misuse in sports needs special attention, since it is naturally present in urine samples. The main goal of this study is to investigate the in vivo metabolism of 7‐keto‐DHEA after a single administration to healthy volunteers and to better describe the relationship between arimistane (androst‐5‐ene‐7, 17‐dione) and 7‐keto‐DHEA after the application of the common routine procedures to detect anabolic steroids in WADA accredited antidoping laboratories. Free, glucuro‐, and sulpho‐conjugated steroids extracted from urine samples obtained before and after the administration of 7‐keto‐DHEA were analyzed by different gas chromatographic (GC)–mass spectrometric (MS) techniques. Gas chromatography coupled to tandem MS to study the effect on the endogenous steroid profile, coupled to isotope ratio mass spectrometry (IRMS) to investigate the potential formation of androgens derived from DHEA and coupled to high resolution accurate mass spectrometry (HRMS) to investigate new diagnostic metabolites. The analysis by IRMS confirmed that there is no formation of DHEA from 7‐keto‐DHEA. Ten proposed metabolites, not previously reported, were described. These include reduced and hydroxylated structures that are not considered part of the steroid profile in antidoping analyses. They showed considerable responses in all fractions analyzed. Some deoxidation reactions (including arimistane formation) were found and most probably can be linked to the sample preparation or instrumental analysis. This is important when interpreting the results after the application of procedures to detect steroids in urine currently used in antidoping laboratories. 7‐keto‐DHEA metabolism in humans for antidoping purposes was studied and unexpected results were found. This could lead to a misinterpretation of the data, depending on the procedure applied and the analytical instrumentation used. Abstract : 7‐Keto‐DHEA metabolism in humans for anti‐doping purposes was studied and non‐expected results have been found. This could lead to a misinterpretation of the data, depending on the procedure applied and analytical instrumentation used.